Analysis of support coupling GBT (Generalized Beam Theory) applied in pipeline systems. (January 2020) - Bianco, Marcelo J.; Habtemariam, Abinet K.; Könke, Carsten; Tartaglione, Fabiola; Zabel, Volkmar
Abstract: Above-ground pipeline systems are subject to a wide range of deformations, such as ovalization and warping, particularly in the neighborhood of a support. A structural analysis, which can fully evaluate these transversal and local effects, can currently be carried out only using shell or solid finite-element models. However, the complete finite-shell element model of a long-distance pipeline system requires a significant amount of time to be modeled and solved. In contrast, generalized beam theory (GBT) has attracted attention as an alternative modeling technique, and it can easily model a pipeline system using beam-finite elements, but with all transversal and local effects. In order to obtain a feasible application of GBT for above-ground pipeline systems, this study presents an extension of GBT with semi-continued arbitrary support to hollow circular cross-sections. The numerical formulation is an alternative recursive approach based on the master-slave method to create a multi-freedom constraint among the high modes of GBT and the springs, which represent the support conditions. An example of its application illustrates the proposed approach and is compared with a complete finite-shell element models. Highlights: Semi-continued arbitrary support for hollow circular cross-section are studied. The Master-Slave Method addresses a recursive approach to obtain a coupled system. The proposed approach requires a minimal amount of GBT's modes. A detailed example shows the proposed approach and compares to shell models.